Novel Loop-Structure-Based CD19/CD22 Dual-Target CAR-T Therapy for High-Risk Diffuse Large B-Cell Lymphoma Presenting with Hemophagocytic Lymphohistiocytosis: A Case Report - Ye Y; Li S; Guo Z; Zhao L; Zhou H; Zhong N; He M; Cao YJ; Liu L (Cancer Management and Research)
Yuan Ye,1,* Shuhong Li,2,* Zhi Guo,1,* Lijun Zhao,2 Huanhuan Zhou,1 Nan Zhong,1 Mingxin He,1 Yu J Cao,2 Liqiong Liu1 1Department of Hematology, Affiliated Nanshan Hospital of Shenzhen University, Shenzhen, Guangdong, 518052, People’s Republic of China; 2State Key Laboratory of Chemical Oncogenomics, Shenzhen Key Laboratory of Chemical Genomics, Peking University Shenzhen Graduate School, Shenzhen, Guangdong, 518055, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liqiong Liu, Department of Hematology, Affiliated Nanshan Hospital of Shenzhen University, Shenzhen, Guangdong, 518052, People’s Republic of China, Email llqwsp@hotmail.com Yu J Cao, State Key Laboratory of Chemical Oncogenomics, Shenzhen Key Laboratory of Chemical Genomics, Peking University Shenzhen Graduate School, Shenzhen, Guangdong, 518055, People’s Republic of China, Email joshuacao@pku.edu.cnObjective: To investigate the efficacy and safety of novel loop-structure-based CD19/CD22 dual-target chimeric antigen receptor T-cell (CD19/CD22 BS LoopCAR-T) therapy in high-risk diffuse large B-cell lymphoma (DLBCL) presenting with hemophagocytic lymphohistiocytosis (HLH).Methods: We analyzed the clinical data of a high-risk DLBCL patient presenting with HLH treated with CD19/CD22 BS LoopCAR-T at the Affiliated Nanshan Hospital of Shenzhen University in December 2023.Results: The patient, a 59-year-old female, was diagnosed with myelodysplastic syndromes with multilineage dysplasia in October 2022. Following six cycles of azacitidine treatment, her bone marrow and hemogram returned to normal, and the disease was stable In August 2023, she presented with recurrent fever for over a month and was diagnosed with high-risk DLBCL stage IVB presenting with HLH. After receiving the HLH-1994 protocol followed by one cycle each of R-CHOP and R-DA-EPOCH regimens, the patient underwent infusion of CD19/CD22 BS LoopCAR-T cells at a dose of 1.73× 108 cells. She experienced a rapid response, developing grade 1 cytokine release syndrome (CRS) and no immune effector cell-associated HLH-like syndrome (IEC-HS), and achieved disease stabilization following aggressive treatment. Bone marrow and peripheral blood flow cytometry at one and three months post-CAR-T therapy showed complete remission (CR). PET-CT at three months post-CAR-T therapy also indicated CR. The patient was followed up until April 2025, and the disease-free survival time after CAR-T treatment exceeded 16 months.Conclusion: The novel CD19/CD22 BS LoopCAR-T therapy is safe and effective in treating high-risk DLBCL patients presenting with HLH.Keywords: hemophagocytic lymphohistiocytosis, diffuse large B-cell lymphoma, CD19/CD22 dual target, chimeric antigen receptor T cells